Extracts of Jasminum sambac flowers fermented by Lactobacillus rhamnosus inhibit H2O2‐ and UVB‐induced aging in human dermal fibroblasts. Issue 4 (3rd December 2020) - Ho, Chih‐Chu; Ng, Shang‐Chuan; Chuang, Ho‐Lin; Wen, Su‐Ying; Kuo, Chia‐Hua; Mahalakshmi, B.; Huang, Chih‐Yang; Kuo, Wei‐Wen
Abstract: Ultraviolet (UV) irradiation is a crucial factor that leads to skin photoaging and results in increased DNA damage, oxidative stress, and collagen degradation. Jasmine flowers have been utilized as a traditional medicine in Asia to treat various diseases, including dermatitis, diarrhea, and fever. Furthermore, the fermented broth of Lactobacillus rhamnosus has been reported to exert protective effects on the skin. In the present study, jasmine flower extract was fermented with L. rhamnosus . We investigated the antioxidant and collagen‐promoting effects on UVB/H2 O2 ‐induced HS68 dermal fibroblast cell damage. The results indicated that treatment with the fermented flower extracts of Jasminum sambac (F‐FEJS) could enhance the viability of HS68 cells. Furthermore, the UVB/H2 O2 ‐induced excessive production of reactive oxygen species, degradation of collagen, activation of MAPKs, including P38, ERK, and JNK, and premature senescence were remarkably attenuated by F‐FEJS in dermal fibroblast cells. The nuclear accumulation of p‐c‐jun, which is downstream of MAPK, and the inactivation of p‐smad2/3, which is one of the crucial transcription factors that enhance collagen synthesis, were reversed in response to F‐FEJS treatment in UVB/H2 O2 ‐exposed cells. Notably, the expression of antioxidant genes, such as HO‐1, and the nuclear translocation of Nrf2 were further enhanced by F‐FEJS in UVB/H2 O2 ‐treated cells. Interestingly, the F‐FEJS‐induced increase in ARE luciferase activity indicated the activation of Nrf2/ARE signaling. In conclusion, our findings demonstrated that F‐FEJS can effectively ameliorate UVB/H2 O2 ‐induced dermal cell aging and may be considered a promising ingredient in skin aging therapy.